Screening for proteinuria and glycosuria among dental patients in Benin City - O. N. Obuekwe; C. D. Odai; C. C. Azodo; O. Akpata; M. A. Ojo (Nigerian Dental Association, 2010)
Objective: To screen for the presence of proteinuria and glycosuria amongst patients attending for routine care in a dental clinic in Benin- City, Edo State, Nigeria. Method: A prospective survey over a period of thirty-six months involving all new consecutive and consenting patients. All consenting patients, yet to have breakfast and with no history of previous screening for proteinuria and glycosuria were screened, using Clinistix test strips. Medical and drug history, and relative risk were given due considerations in patient selection. Athletes, specifically marathon runners were excluded. Findings were analysed as simple frequency tables and percentages. Results: A total of four thousand, four hundred and ninety patients who attended the Oral Diagnosis Clinic of the Faculty of Dentistry, University of Benin and met inclusion criteria were screened. Fifty three (1.2%) positive cases of glycosuria were recorded. The male: female ratio was 1:1.1 and the majority of patients (49%) were in age group 19-29 years. Forty three (1.0%) were positive, for proteinuria. There was a preponderance of females (1.7%) over males (0.8%) and most patients (65.1%) were in the 19-29 years age group. Conclusion: Most patients were asymptomatic and accepted a referral to the physician. It is recommended for the benefit of attending patients to the dental surgery to include routine urine analysis for glucose and protein in addition to the usual assessment of vital signs.